Aortic Remodeling and Human Immunodeficiency Virus Infection: Two Case Reports - Jospin Makani Bassakouahou; Christian Kouala Landa; Eric Kimbally-Kaky; Paterne Bakekolo; Bertrand Ellenga Mbolla; Meo Ikama (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
The human immunodeficiency virus infection is a pathology responsible for chronic inflammation leading to vascular remodeling. We report two cases of patients living with human immunodeficiency virus, with severe aortic insufficiency and dilation of the aorta. Heart failure dominated the clinical signs. The chest x-ray showed cardiomegaly and an enlarged mediastinum. Doppler echocardiography showed, in addition to severe aortic leakage, unusual dilation of the aorta and dissection of the ascending aorta in one of the patients. The computed tomography of the aorta revealed more details about the accuracy and extent of aortic lesions. One of the patients underwent surgical treatment.